ANTI-INFLAMMATORY ACTIVITY OF ROOT AND FRUIT OF GOKSHURA (TRIBULUS TERRESTRIS LINN.) IN ALBINO RATS - Sudheendran, *Ankitha; Shajahan, M.A.; S, Premlal. (International Journal of Ayurveda and Pharma Research, 2017)
Gokshura Moola (root of Tribulus terrestris Linn.) is one of the ingredients of the group of ten medicinal plant roots called Dasamoola. It is a major ingredient of Ayurvedic formulations so that the Ayurvedic manufacturing industry is consuming them in abundantly. Instead of roots, the fruits of Tribulus terrestris is roughly using in all the preparations of Dasamoola. In Ayurvedic classics Gokshura is said to be useful in the treatment of dysurea (Mutrakrichra), inflammation (sopham), renal calculi (Asmari), cardiac diseases (Hridroga), rheumatoid arthritis (Amavata), rejuvenation (Rasayana), aphrodisiac (Vajeekarana), etc. Ancient Ayurvedic literature opines that the properties and actions attributed to one part of the plant will be the same for the other parts too. If the fruit of the plant is equally effective as the root then the destruction of the whole plant can be prevented. Hence, the present study is carried to evaluate and compare the anti-inflammatory activity of both root and fruit Kashaya (decoction) experimentally by- Carrageenan induced rat paw oedema method with Diclofenac sodium (20 mg/kg) as standard. The results were analysed statistically by ANOVA and LSD post hoc pair wise comparison test. Both root and fruit of Gokshura, showed significant anti inflammatory activity in albino rats. But the root of Gokshura (Tribulus terrestris Linn) showed a greater anti inflammatory action in comparison to its fruit. Thus the current substitution of Gokshura roots with fruits can be substantiated by this study but effect may be less compared to root part.